Considerations for Balance Between Fundamental Treatment and Improvement of Quality of Life of Pediatric Thyroid Cancer Patient: Comparative Analysis With Adult Using Propensity Score Matching - Ji Young You; Se-Woong An; Hoon Yub Kim; Da Won Park; Hyung Kwon Byeon; Serena Patroniti; Gianlorenzo Dionigi; Gianlorenzo Dionigi; Ralph P. Tufano (Frontiers Media S.A., 2022)
BackgroundThyroid cancer is very rarely observed in children and adolescents, some reports have shown that the long-term outcome of treatment is better than that of adult patients, despite many treatment failures or a high risk of recurrence. This study considers whether it is appropriate to treat pediatric thyroid cancer patients aggressively, as per the ATA guidelines, based on the balance between the fundamental treatment of thyroid cancer and the improvement of the long-term quality of life of pediatric patients.MethodsA total of 1,950 patients were recruited, including 83 pediatric and 1,867 adult patients, who were diagnosed with thyroid cancer and underwent surgical treatment at one of our medical center hospitals from March 2000 to January 2020.ResultsSixty-nine pairs of pediatric and adult patients were matched in a ratio of 1:2 through propensity score matching. When compared through propensity score matching, there was no significant difference in prognosis such as recurrence rate in children and adults at the same stage.ConclusionThis study showed that the prognosis of both pediatric and adult patients who underwent a total thyroidectomy and lobectomy was not significantly different. If more pediatric patients can be considered for the less-aggressive lobectomy than a total thyroidectomy through various preoperative examinations and meticulous pre-diagnosis, it may be possible to properly determine the balance between improving long-term quality of life while providing fundamental cancer treatment.